Pelatihan Teknik Vertikultur Budidaya Ubi Jalar Bagi Kelompok Warga di Kelurahan Bila, Kabupaten Soppeng - Muis, Abd.; Rachmawaty, Rachmawaty; Hiola, St. Fatmah; Arifin, Arifah Novia (Jurnal Abdi Negeriku, 2022)
Sweet potato (Ipomoea batatas) is cultivated in Indonesia by monoculture and intercropping. Sweet potato cultivation vertically is not yet popular. The Community Partnership Program (PKM) aims to provide community groups with knowledge and skills about verticulture techniques for sweet potato cultivation. This training was carried out in the Bila Village through the preparation stage for licensing, preparation of materials and tools, the training stage was carried out using the lecture method and brochure literacy, then demonstration by showing a video, and the performance stage of preparing planting media and vertical planting of seeds, and the final stage was carried out accompaniment. The results obtained are a series of training activities followed carefully by all participants. Participants responded enthusiastically based on their readiness to do it themselves in their respective yards. The results of the assessment showed that the participants' knowledge increased from not knowing then to knowing how to cultivate sweet potato vertically. There were 90.5 percent of participants stated that they would apply the verticulture system of sweet potato cultivation techniques, all of them (100%) stated that the tools and materials for the verticulture system cultivation could be prepared and could do it independently, and 80.95 percent stated that they wanted to teach the verticulture system cultivation techniques to other citizens. These results illustrate that training in PKM carried out with assistance provided benefits for community groups in Bila Village.